Generator Mini dengan Prinsip Termoelektrik dari Uap Panas Kondensor pada Sistem Pendingin - Ryanuargo .; Syaiful Anwar; Sri Poernomo Sari (Universitas Syiah Kuala, 2013)
In daily life, it is often found that office buildings and shopping centers use air conditioning system (AC Central) for room cooling. The refrigerant in the cooling system releases the heat into the air with the help of the motor fan. In order to release the heat faster, the condenser pipe winding is designed and equipped with fins. The heat released from the condenser will be discharged to the air. This will lead to global warming if large numbers of air conditioning system are used. In this case, thermoelectric technology is a main alternative solution that can be implemented. Thermoelectric converts heat energy directly into electrical energy. Therefore, in this paper, we design a simple power system by utilizing waste heat energy from a condensor based on thermoelectric method. Based on the result of the experiment, an average temperature of 34°C results in voltage of 3.14 Volts and power of 0.16 Watts.